Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^3-3x^2+1-3x=\left(x^3+1\right)-3x^2-3x\)
\(=\left(x+1\right)\left(x^2-x+1\right)-3x\left(x+1\right)=\left(x+1\right)\left(x^2-x+1-3x\right)=\left(x+1\right)\left(x^2-4x+1\right)\)
\(x^8+3x^3+1\)
\(=x^8-x^4+4x^4+4\)
\(=\left(x^4-1\right)\cdot\left(x^4+1\right)+4\cdot\left(x^4+1\right)\)
\(=\left(x^4+1\right)\cdot\left(x^4-1+4\right)\)
\(=\left(x^4+1\right)\cdot\left(x^4+3\right)\)
\(=x^2+x+2x+2=x\left(x+1\right)+2\left(x+1\right)=\left(x+1\right)\left(x+2\right)\)
\(=x^2+2x\cdot\frac{1}{2}+\frac{1}{4}-\left(\frac{\sqrt{23}}{2}i\right)^2\)
\(=\left(x+\frac{1}{2}\right)^2\)\(-\left(\frac{\sqrt{23}}{2}i\right)^2\)
\(\left(x+\frac{1}{2}-\frac{\sqrt{23}}{2}i\right)\left(x+\frac{1}{2}+\frac{\sqrt[]{23}}{2}i\right)\)
\(x^2+5x-2=\left(x^2+2.x.\frac{5}{2}+\frac{25}{4}\right)-\frac{25}{4}-2=\left(x+\frac{5}{2}\right)^2-\frac{33}{4}\)
\(=\left(x+\frac{5}{2}\right)^2-\left(\frac{\sqrt{33}}{2}\right)^2=\left(x+\frac{5}{2}-\frac{\sqrt{33}}{2}\right)\left(x+\frac{5}{2}+\frac{\sqrt{33}}{2}\right)\)
\(=\left(x+\frac{5-\sqrt{33}}{2}\right)\left(x+\frac{5+\sqrt{33}}{2}\right)\)
\(x^4+2002x^2-2001x+2002\)
\(=x^4+2002x^2+x-2002x+2002\)
\(=\left(x^4+x\right)+\left(2002x^2-2002x+2002\right)\)
\(=x\left(x^3+1\right)+2002\left(x^2-x+1\right)\)
\(=x\left(x+1\right)\left(x^2-x+1\right)+2002\left(x^2-x+1\right)\)
\(=\left(x^2-x+1\right)\left[x\left(x+1\right)+2002\right]\)
\(=\left(x^2-x+1\right)\left(x^2+x+2002\right)\)
\(x^4-x^2+2x+2\)
\(=x^4-2x^3+2x^2+2x^3-4x^2+4x+x^2-2x+2\)
\(=\left(x^4-2x^3+2x^2\right)+\left(2x^3-4x^2+4x\right)+\left(x^2-2x+2\right)\)
\(=x^2\left(x^2-2x+2\right)+2x\left(x^2-2x+2\right)+\left(x^2-2x+2\right)\)
\(=\left(x^2-2x+2\right)\left(x^2+2x+1\right)\)
\(=\left(x^2-2x+2\right)\left(x+1\right)^2\)
\(x^2+3x+2=x^2+2x+x+2\)
\(=x\left(x+1\right)+2\left(x+1\right)=\left(x+2\right)\left(x+1\right)\)